Giant Ileal Conduit Stone: Feasibility of Endoscopic Lithotripsy: A Case Report and Review of Literature - Sharaf Ala’a; Sahadevan Kanagasabai (Journal of Medical and Surgical Urology, 2018)
Ileal conduit has been considered the urinary diversion of choice following radical cystectomy although orthotopic bladder substitution is gaining popularity. Urinary diversions are associated with complications including stone formation in up to 54%. We report the management of the largest ileal conduit stone reported in the literature.
Keywords: ileal condiut